X-ray Attenuation and Reduction of Backscattered Radiation - Naji, A. T.; Jaafar, M. S.; Ali, Esmail Abdo Mohammed; Al-Ani, S. K. J. (Canadian Center of Science and Education, 2016)
This paper reports the comparative study of X-ray attenuation using different materials which can be utilized to design anti-backscattered grids and radiation protection shields. The characteristics of X-ray attenuation in several materials, namely, lead, copper, iron steel, and aluminum, are investigated under diverse exposure parameters to measure their ability to attenuate incident X-ray and their capability to reduce backscattered X-ray. Lead and iron steel shields exhibit the best abilities in attenuating X-ray, whereas aluminum shield shows the least attenuation ability. This study proposes a design of a unique method for assessing the backscatter X-ray dose. The iron steel grid based on iron steel plate provides the best value in reducing backscattered radiation (up to 34.78%) compared with other conventional plate materials.